Experimental Research Concerning the Contact Patch of the Double Worm Face Gear. (2016) - Ciotea, Margareta; Boloş, Vasile
Abstract: This paper aims to present the results of an experiment linked to positioning and the contact patch size of a double worm face gear. The worm face gear tested is provided with one-piece double worm face wheel that involves specific adjustment difficulties. Couple of used materials is the hard steel for the worm and the gray cast iron for the wheel. We mention technological conditions for obtaining the worm and the worm wheel. The contact patch completeness check gear flanks results was done on a test stand using training gear on both sides of succession worm knowing the fact that they show different pressure angles. The contact patch has different values obtained on the two sides of the flanks, the smaller pressure angle ensuring better conditions of engagement.